2016
DOI: 10.1111/his.13071
|View full text |Cite
|
Sign up to set email alerts
|

Molecular alterations in indolent, aggressive and recurrent ovarian low‐grade serous carcinoma

Abstract: Despite limited case numbers, it appears that current molecular testing is inferior to a pathological parameter or protein expression in predicting the outcome of LGSCs. Prediction of outcome based on the primary tumour may be confounded by additional changes acquired over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 33 publications
3
20
0
4
Order By: Relevance
“…Additionally, RAS mutations were often associated with RAS copy number gain. As previously reported [24, 46, 50] we also detected multiple and distinct genomic alterations affecting other genes related to the MAPK cell signaling pathway. It is worth noting that the individual comparison of genomic profiles between LGSC cultures showed substantial variations in the types of gene mutations and copy-number alterations, indicating widespread molecular differences in LGSC tumors between patients.…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, RAS mutations were often associated with RAS copy number gain. As previously reported [24, 46, 50] we also detected multiple and distinct genomic alterations affecting other genes related to the MAPK cell signaling pathway. It is worth noting that the individual comparison of genomic profiles between LGSC cultures showed substantial variations in the types of gene mutations and copy-number alterations, indicating widespread molecular differences in LGSC tumors between patients.…”
Section: Discussionsupporting
confidence: 85%
“…More recently, NRAS mutations were described in LGSOC. Five studies identified 12 NRAS mutations (either at Q61R or Q61K) in a total of 118 cases, resulting in an average frequency of 9.3% [7], [9], [26], [27], [28]. We found three NRAS mutations in our series.…”
Section: Discussionmentioning
confidence: 46%
“…We have previously shown that progesterone receptor (PGR) expression is a favorable prognostic factor in LGSC . Perhaps PGR and p16 status could help to stratify LGSC regarding prognosis . Another consideration is the possible predictive utility of absent p16 expression for CDK4 inhibitors as suggested in clinical trials for breast and other cancers .…”
Section: Discussionmentioning
confidence: 99%